Диспозитивність як принцип цивільного процесуального права та його реалізація при розгляді справ про визнання шлюбу недійсним - Войтенко, Т.В. (Альманах права, 2012)
В статті розкрито зміст принципу диспозитивності як одного з принципів цивільного процесуального права. На прикладі розгляду справ про визнання шлюбу недійсним автор розкриває механізм дії даного принципу. В статье раскрыто содержание принципа диспозитивности как одного из принципов гражданского процессуального права. На примере дел о признании брака недействительным автор раскрывает механизм действия этого принципа. The realization of justice on civil cases is impossible without scientific research and theoretical analysis of the valued measuring fundamental principles leading ideas of civil judicial law — principle of the civil legal proceeding. In a scientific point of view expediency of theoretical study of principle of discretionary is that it serves as a tool
for scientific analysis of the functioning civil procedure legal relationships in general and realizations of the civil procedure in particular. An author in the article analyzes the scientific approaches to understanding the principle of discretionary, validity
its valued loading as a fundamental principle of civil procedure law and reveals the practical value of this principle on the example of adjudication by the court cases of declaration marriage as invalid and compares discretionary and activity of the court in the present conditions of civil proceedings in Ukraine. Researching this topic the authors is considering the principle of discretionary as valued measurement of civil procedural law.